PLANT DIVERSITY OF QUANG TRUC FOREST IN DAK NONG PROVINCE, VIETNAM - Thanh Trang, Pham; Thi Thu, Nguyen; Thanh Luong, Hoang (Journal of Forestry Science and Technology, 2017)
Quang Truc forest (QTF) is a remote area in the South-West of Dak Nong province, Vietnam, which is well known for valuable timber species representative for central highland of Vietnam with different globally and nationally threatened species. However, the general understanding of plant diversity of QTF has been still poorly known. The objectives of this paper are to figure out the plant diversity of QTF and compare that with other protected forest areas in Dak Nong province, in order to provide scientific evidences for conservation and sustainable development. The desk study, field work on transect sampling and PRA surveys were conducted to assess plant diversity in QTF in comparison with Ta Dung and Nam Nung Nature Reserves, Dak Nong province. A total of 654 plant species belonging to 132 families and five phylas were found for QTF from our current investigation. Also, there are up to 34 threatened species presented in QTF, 17 of which are listed in IUCN Red List, and 26 species listed in Viet Nam Red Book (2007). The finding of our research also indicated that number of plant families and species in QTF is lower than that of Ta Dung, but it is still significant compared to Nam Nung Nature Reserve.